Performance Achievement of Sharia Sharia Banks in Indonesia with the MSI Approach: Government Vs Private Owned - Ramadhan, Malinda; Triyono, Triyono; Sasongko, Noer (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The prevalence of Islam among the Indonesian population has significant prospects for advancing Islamic banking institutions. The categorization of Islamic banks according to ownership is bifurcated into private and public ones. These researchers look at how well Islamic banks from both categories are doing using the Maqashid Sharia Index (MSI). It is essential to examine whether there are any variations in the performance of MSI (Muslim-owned banks) before and following the merger of state-run businesses (SOEs), as this merger impacts the structure of SOE-owned Islamic banks. The Mann-Whitney U-test, a quantitative approach, was employed to analyze data extracted from the financial statements of Islamic banks spanning the years 2016 to 2022. The results indicate performance variations between private and public Islamic banks, as measured by the MSI. Islamic banks that are privately owned demonstrated superior performance in terms of Maqashid Sharia, as seen by their dominance in the top five rankings. The research findings indicate that government-owned Islamic banks excel in promoting educational objectives, but private-owned Islamic banks demonstrate supremacy in advancing goals related to benefit and justice. The performance of state-owned Islamic banks in terms of MSI before and following the merger is equal.